My mom - Browne, Anthony, 1946- (New York : Farrar, Straus, Giroux, 2005)
A child describes the many wonderful things about his mom who can make anything grow, roar like a lion, and be as comfy as an armchair.
First published: Great Britain : Doubleday, 2005.
Publisher's Weekly.
School Library Journal.
Wilson's Children.
2.9.
2.9
Keywords: Mother and child -- Juvenile fiction; Mothers -- Juvenile fiction; Mother and child -- Fiction; Mothers -- Fiction; Mother-child relationship -- Fiction; Mothers -- Fiction